Estimation of the infectious viral load required for transfusion‐transmitted human T‐lymphotropic virus type 1 infection (TT‐HTLV‐1) and of the effectiveness of leukocyte reduction in preventing TT‐HTLV‐1. Issue 2 (30th April 2015) - Sobata, R.; Matsumoto, C.; Uchida, S.; Suzuki, Y.; Satake, M.; Tadokoro, K.
<x xml:space="preserve">Abstract</x> Background and Objectives The risk of transfusion‐transmitted human T‐lymphotropic virus type 1 infection (TT‐HTLV‐1) after prestorage leucocyte reduction (LR) remains unknown, as the proviral load in the blood component that would cause TT‐HTLV‐1 is undetermined. On the basis of the distribution of HTLV‐1 proviral load among HTLV‐1‐sero‐positive blood donors, we attempted to estimate the proviral load for transfusion‐related infectivity. We also discuss the effectiveness of LR in preventing TT‐HTLV‐1. Materials and Methods The HTLV‐1 proviral load in 300 HTLV‐1‐sero‐positive blood donors was determined by real‐time polymerase chain reaction analysis. The proviral load required for transfusion‐related infectivity was estimated using historical TT‐HTLV‐1 frequency data from a retrospective study on patients who had received blood from HTLV‐1‐sero‐positive blood donors and the distribution pattern of HTLV‐1 proviral load among blood donors. Results HTLV‐1 proviral loads ranged between <0·01 and 25·0 copies per 100 leucocytes. Historical data showed TT‐HTLV‐1 frequency to be 80%. Assuming that 80% of the 300 sero‐positive samples are infectious, it is estimated that the transfer of ≥9 × 104 cells containing the HTLV‐1 provirus is required to establish TT‐HTLV‐1. Conclusion The residual number of HTLV‐1‐infected cells after LR is substantially lower than the viral load necessary for TT‐HTLV‐1. LR therefore appears to be effective in minimizing the incidence of TT‐HTLV‐1.